Evaluasi sifat putih telur ayam pasteurisasi ditinjau dari pH, kadar air, sifat emulsi dan daya kembang Angel Cake - Nia Agustina; Imam Thohari; Djalal Rosyidi (Faculty of Animal Science, Universitas Brawijaya, 2013)
The purpose of this research was to determine effect of pasteurized egg and storage time on pH, water content, characteristics of emulsion, volume of angel cake and determine the best treatment. Method was used pasteurzation research was a experiment factorial Randomized Block Design (RBD) with 2x3 treatment and 3 replication. The data was analized by using analysis of variance continued by Honestly Significant Difference (HSD). The results showed that the interaction pasteurization and storage time was a very significant effect (P<0.01) on pH, water content, characteristics of emulsion and volume of angel cake. The conclusion of this research the effect storage time increase on pH, decrease characteristics of emulsion and volume of angel cake. Interaction pasteurization and storage time has not effect on water content. The best treatment is not pasteurization and storage time. The suggestion be can given should to use fresh eggs, as well as further research needs to be done to test the others like texture and organoleptic. Keywords : Egg, pasteurization, angel cake